(untitled) (Biological Sciences - PJSIR, 2024)
Clone PB 260 firstly planted in 1975 and popular due to its excellent vigor and productivity during maturity (1.5-2 tonnes/ha10), the dense foliage reduced extensive weeding and is resistance against major leaf diseases. The knowledge on the bark recovery rate is very important to maintain high yield of latex production on rubber plantation. The study which was conducted on the experimental farm of Rubber Research Institute, Sungei Putih, Deli Serdang, north Sumatra, Indonesia was aimed to obtain the optimum combination concentration of growth regulators (NAA+ and kinetin) and various oleo-chemicals to accelerate bark recovery and response of bark recovery rate for rubber clones PB 260. Factorial randomized block design, which consists of two factors, namely growth regulatorcon centrations (N1=50 ppm NAA+ + 50 ppm kinetin; N2=100 ppm NAA+ + 50 ppm kinetin; N3=150 ppm NAA+ + 50 ppm kinetin) and oleo- chemicals (01=palmitic acid; 02=oleic acid and 03=stearic acid) were used in this study. The parameters measured were the number of latex vessels, skin thickness, sucrose levels, thiol levels, inorganic phosphate level, latex yield and total solid content (TSC). The results showed that growth regulator concentrations significantly affect the number of latex vessels but did not significantly affect the skin thickness, sucrose levels, thiol levels, inorganic phosphate levels, latex yield and total solid content (TSC). The most optimum growth regulator combination was N2 at various parameters observed. 0leo-chemicals application showed significant effect on the number of latex vessels, skin thickness and latex yield, but showed no significant effect on levels of sucrose, thiol levels, inorganic phosphate level and total solid content (TSC). Thus, application of growth regulator and oleo-chemicals are beneficial to accelerate bark recovery rate in order to maintain latex production on rubber plantation.